Study of haematological abnormalities in HIV infected patients and its correlation with CD4 counts - Dhal, Nirjharini; Panda, Sridhar; Mohapatra, Namita; Pattanayak, Naresh C.; Pattanaik, Rohan (International Journal of Research in Medical Sciences, 2018)
Background: To study and correlate the haematological abnormalities with CD4 cell counts in HIV infected patients diagnosed on OPD basis in S.C.B Medical College, Cuttack, before they are initiated on Antiretroviral (ARV) therapy. Methods: A 100, ELISA positive, untreated HIV patients were included in the study while those patients with history of any haematological disease, Chronic Kidney Disease (CKD), Chronic Liver Disease (CLD), underlying malignancy or on chemotherapy were excluded. Following clinical evaluation, haemoglobin levels (Hb. %), Total Leucocyte Count (TLC), Differential Leucocyte Count (DLC), Erythrocyte Sedimentation Rate (ESR), Platelet Count (PC), CD4 counts (by flow cytometry) and peripheral smear examination was done. They were staged as per WHO clinical staging guidelines given by NACO and statistical analysis was drawn by Fischer Exact Test and association between CD4 counts and haematological abnormalities were inferred. Results: The mean age of the patients was found to be 36.85±6.2 years with males (63%), married (80%) and rural population (78%) showing commonest mode of transmission of the virus as heterosexual route (94%). Most common clinical finding was found to be pallor (68%) with majority in stage III of AIDS. Mean TLC count was found to be 5872±2210 cells/mm 2.40% had leucopenia on TLC and 29% had neutropenia, 30% lymphocytopenia and 20% monocytopenia on DLC. Mean CD4 count was 89 cells per microliter and 79% were anaemic. CD4 counts did not statistically correlate either with WHO staging or cytopenias or haemoglobin levels. However, there was positive association between CD4 counts with anaemia, WHO stages of AIDS, lymphocytopenia and monocytopenia in this study. Conclusions: In this study we could ascertain that, majority were in WHO stage III of AIDS with CD4 counts <200 cells per microliter and blood findings of various cytopenias and anaemia. From our findings, we could correlate between WHO stage of AIDS, CD4 counts and haematological abnormalities thus, establishing the essence of our study.